Synthesis and Characterization of Biotene: A New 2D Natural Oxide From Biotite. Issue 27 (2nd June 2022) - Mahapatra, Preeti Lata; Tromer, Raphael; Pandey, Prafull; Costin, Gelu; Lahiri, Basudev; Chattopadhyay, Kamanio; P. M., Ajayan; Roy, Ajit K.; Galvao, Douglas S.; Kumbhakar, Partha; Tiwary, Chandra Sekhar
Abstract: In this work, the synthesis and characterization of ultrathin metal oxide, called biotene, using liquid‐phase exfoliation from naturally abundant biotite are demonstrated. The atomically thin biotene is used for energy harvesting using its flexoelectric response under multiple bending. The effective flexoelectric response increases due to the presence of surface charges, and the voltage increases up to ≈ 8 V, with a high mechano‐sensitivity of 0.79 V N −1 for normal force. This flexoelectric response is further validated by density functional theory (DFT) simulations. The atomically thin biotene shows an increased response in the magnetic field and thermal heating. The synthesis of two‐dimensional (2D) metal‐oxide biotene suggests a wealth of future 2D‐oxide material for energy generation and energy harvesting applications. Abstract : Biotene, a 2D material with a minimum thickness of 2 nm, is introduced. Flexoelectricity allows the thin sheets to convert mechanical energy (through tapping, bending, and magnetic force application) into electrical energy. This unique 2D material harvests 17V when force and heat are applied simultaneously, making it a promising resource for next‐generation energy collecting devices.